The Effectiveness of Summary Writing Strategy with Bloom Taxonomy Questions - Dewi, Atika Kumala; Cahyono, Bambang Yudi; Zubaidi, Nanang (Lectura : Jurnal Pendidikan, 2024)
English as a Foreign Language (EFL) evolves to include reading, writing, listening, and speaking. Writing is crucial in higher education for academic report preparation and final project requirements by developing a proper summary. However, there is a lack of research on enhancing summary writing skill in EFL contexts. The Bloom taxonomy model can help to develop students' cognitive analysis. Therefore, this study aims to examine the difference in summary writing skills among EFL students taught using Bloom taxonomy questions. To achieve this aim, a quasi-experimental method was employed by two groups: an experiment group and a control group. The experimental group was taught summary writing strategies using Bloom taxonomy questions, while the control group received a control group. Both groups were given a pre-test and a post-test before and after the treatment. The results showed that the pre-test scores and post-test scores were similar between the experimental and control groups. However, the paired sample t-test showed a significant difference between pre-test and post-test scores in the experimental group, indicating a significant increase in results. The study provided valuable insights into the effectiveness of different treatment methods in improving students' summary writing skills. In conclusion, the study shows that Bloom taxonomy questions can significantly enhance students' summary writing skills, as they are more attractive, hierarchical, and cognitively domain-specific than conventional teaching methods. The experimental group achieved higher mean scores. The results suggest that EFL teachers should select appropriate source texts and future research should consider locations and subjects.